(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The aim of this work is to study the pattern of the spatial distribution of the population of Thyphlodromus pyri Scheuten in a Lombard vineyard. A two-stage sampling pian has been performed with the purpose to describe the distribution of the individuals of this species during the whole vegetative season of 1995. The analysis of collected data has shown that the distribution of the population of T. pyri is not homogenous. In fact, differences have been found in the average abundance per sampling unit in the parts of the vineyard located on the border with bush and arboreal vegetation. A non-homogenous distribution has been also registered along the vertical dimension of the vine-shoots with a clear preference for the lower part of the latter. Finally, it has been observed that, using the single leaf as a spatial unit of sampling, the spatial pattern of the individuals is aggregative. The study of the temporal dynamics of aggregation has brought to light the tendency towards an intensification of aggregation intensity during the vegetative season.